ANALYSIS OF PRODUCT PREFERENCE OF CHITATO AND LAYS POTATO CHIPS - Rafadi Khan Khayru; Didit Darmawan; Misbachul Munir (Transpublika Publisher, 2021)
This study aims to determine differences in consumer preferences for potato chip products. Two well-known local brands, Chitato and Lays, come from the same manufacturer and it is interesting to observe the differences in consumer preferences for the two. These two brands already have a high level of brand awareness in the market as evidenced by a larger market share than other brands. Samples were taken as many as 94 respondents with a sampling technique with an accidental sampling approach. The results of the questionnaire were analyzed by SPPS statistics in the form of validity and reliability tests, Paired Sample t-test to see the significance of differences in consumer preferences for potato chips products. The results of hypothesis testing indicate that the consumer preferences of the Chitato brand and the Lays brand are not significantly different. According to respondents as consumers, the selection of potato chip products is the same as buying so that it is the task of marketers to strengthen product attributes and the brand strength of each product.